2001
DOI: 10.1207/s15328023top2803_10
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing Lecture with Simulations in Developmental Disabilities: SIDD Software

Abstract: We evaluated Simulations in Developmental Disabilities (SIDD), a multimedia software program that provides students with practice in behavioral assessment and treatment decisions for persons with developmental disabilities. Following a lecture on clinical strategies, students in an experimental group received instruction with SIDD whereas students in the control group did not. We collected assessments of students' clinical knowledge before and after the lecture, immediately after training, and several weeks la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Students who completed course evaluations were quite positive about the tutorials and emphasized components that have been favorably evaluated in other studies-practice exercises with immediate feedback, ability to isolate key concepts, visual presentation of material, and unlimited access to the material (Desrochers et al, 2001;Mitchell & Jolley, 1999;Varnhagen & Digdon, 2002;Wilson & Harris, 2002;Worthington et al, 1996). Students suggested additional tutorials on topics within analysis of variance, a recommendation that was consistent with the finding that the factorial analysis of variance tutorial was the only one with no demonstrable impact on learning.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Students who completed course evaluations were quite positive about the tutorials and emphasized components that have been favorably evaluated in other studies-practice exercises with immediate feedback, ability to isolate key concepts, visual presentation of material, and unlimited access to the material (Desrochers et al, 2001;Mitchell & Jolley, 1999;Varnhagen & Digdon, 2002;Wilson & Harris, 2002;Worthington et al, 1996). Students suggested additional tutorials on topics within analysis of variance, a recommendation that was consistent with the finding that the factorial analysis of variance tutorial was the only one with no demonstrable impact on learning.…”
Section: Discussionmentioning
confidence: 59%
“…Research has shown that effective use of multimedia can increase student learning (Erwin & Rieppi, 1999;Fletcher-Flynn & Gravatt, 1995;Forsyth & Archer, 1997;Kazmerski & Blasko, 1999;McNeil & Nelson, 1991) and instructors are increasingly encouraged to incorporate multimedia into classroom teaching. Computerized demonstrations that are used for active learning exercises during class sessions and for supplementary, out-of-classroom learning and review have been developed for teaching: 1) introductory psychology (Chaparro & Halcomb, 1990;Worthington, Welsh, Archer, Mindes, & Forsyth, 1996), 2) research methods (Kazmerski & Blasko, 1999;Varnhagen & Digdon, 2002), 3) clinical diagnosis (Desrochers, House, & Seth, 2001;Jachna, Powsner, McIntyre, & Byck, 1993), 4) decision-making (Misale, Gillette, & del Mas, 1996), 5) perception and cognition (Neuhoff, 2000); 6) social psychology (Sherman, 1998), 7) behavioral principles (Lambert, 1987;Silva, Yuille, & Peters, 2000), and, most relevant for the current work, 8) statistics (Aberson, Berger, Healy, Kyle, & Romero, 2000;Britt, Sellinger, & Stillerman, 2002;Franklin & Cooley, 2002;Hurlburt, 2001;Richardson & Segal, 1998;Warner & Meehan, 2001;West & Ogden, 1998). Students consistently give favorable reviews to these computerbased learning resources emphasizing their interactive nature, ease of use, graphical presentation of material, and the ability to review concepts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Koch and Gobell (1999) found that Web-based tutorials led to improved accuracy regarding decisions about design issues and the correct choice of statistics in an advanced course on research methods and statistics. Desrochers, House, and Seth (2001) reported higher scores among students who used Web-based tutorials to apply knowledge of assessment and intervention to a novel clinical situation compared to students who learned the material in a lecture-only format. Similarly, Wilson and Harris (2002) evaluated the use of interactive tutorials in an introductory psychology class and found that students who learned from the Web-based tutorial scored better on exams than students who learned only from classroom lectures.…”
Section: Student Performance Using Web-based Tutorialsmentioning
confidence: 99%
“…Desrochers, House and Seth (2001) examined the use of multimedia software to supplement lecture material. Following a lecture on the use of clinical techniques for persons with developmental disabilities, subjects in the experimental group received supplemental instruction via multimedia software, whereas subjects in a control group did not.…”
mentioning
confidence: 99%